2014
DOI: 10.7567/apex.7.085502
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of GaN films grown on multilayer graphene films by pulsed sputtering

Abstract: GaN films were grown on a multilayer graphene (MLG)/amorphous SiO2 stack by pulsed sputtering deposition and their structural properties were investigated. The GaN films on MLG show high c-axis orientation. In addition, the GaN films exhibit coexisting zincblende and wurtzite phases, but the zincblende phase is suppressed by the insertion of AlN interlayers. The polarity control of the GaN films was demonstrated using AlN interlayers with and without surface oxidation. These results indicate that the proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…The detailed growth conditions are described elsewhere. 13,16,18 The film surfaces were investigated by scanning electron microscopy (SEM), atomic force microscopy (AFM), reflection high-energy electron diffraction (RHEED), and Al Kα X-ray photoelectron spectroscopy (XPS). The sharpness of the heterointerfaces between GaN and Hf was investigated using X-ray reflectivity (XRR).…”
Section: -mentioning
confidence: 99%
“…The detailed growth conditions are described elsewhere. 13,16,18 The film surfaces were investigated by scanning electron microscopy (SEM), atomic force microscopy (AFM), reflection high-energy electron diffraction (RHEED), and Al Kα X-ray photoelectron spectroscopy (XPS). The sharpness of the heterointerfaces between GaN and Hf was investigated using X-ray reflectivity (XRR).…”
Section: -mentioning
confidence: 99%
“…Fabrication of high‐performance GaN devices such as LEDs and transistors requires a technique allowing to control the GaN polarity. It has been recently reported that GaN growth on a surface‐oxidized AlN layer resulted in the formation of Ga‐polar GaN . Herein, AlN interlayers were introduced on the HfN layers and subsequently surface‐oxidized by annealing under air at 200 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Further, GaN, InGaN, and AlN films were grown by PSD. The detailed growth conditions are described elsewhere [3], [4]. The grown films were characterized by X-ray diffraction (XRD) using a Bruker D8 diffractometer and by electron backscatter diffraction (EBSD) using an INCA Crystal EBSD system (Oxford Instruments).…”
Section: Growth and Characterization Of Gan Filmsmentioning
confidence: 99%